2009
DOI: 10.1016/j.bbi.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

The glial activation inhibitor AV411 reduces morphine-induced nucleus accumbens dopamine release

Abstract: Glial activation has recently been discovered to modulate several effects of morphine, including analgesia, tolerance, and dependence. The present studies extend this line of investigation by exploring whether glial activation may also affect extracellular levels of dopamine (DA) in the nucleus accumbens (NAc) shell, a neurochemical corollary of morphine-induced drug reward, during a challenge dose of morphine in experiments both with and without precipitated withdrawal. Morphine or vehicle was administered s.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 45 publications
1
61
0
Order By: Relevance
“…Alterations in glial glutamate transporter expression have also been shown to substantially modify opioid reward and dependence [28,29]. Attenuation of CNS proinflammation and associated reductions in IL-1b expression has been shown to not only reduce opioid reward behaviour and reward neurochemistry, but also the presentation of withdrawal behaviours [24,30,37].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Alterations in glial glutamate transporter expression have also been shown to substantially modify opioid reward and dependence [28,29]. Attenuation of CNS proinflammation and associated reductions in IL-1b expression has been shown to not only reduce opioid reward behaviour and reward neurochemistry, but also the presentation of withdrawal behaviours [24,30,37].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, attenuation of CNS proinflammation significantly reduced the rewarding effects of morphine [25,26]. Hutchinson et al [24] also reported that in rats, minocycline, an attenuator of CNS proinflammation, significantly reduced morphine-induced behavioural reward, whereas Bland et al [30] showed that glial attenuation reduced the neurochemical indices of reward. Two different CNS immune inhibitors, minocycline and AV411, which are capable of reducing the opioid-induced proinflammatory activation but have distinct functional mechanisms, can both reduce opioid withdrawal [24,37].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ibudilast is a phosphodiesterase inhibitor that suppresses pro-neuroinflammatory glial responses [16, 249]. In preclinical studies, minocycline and ibudilast have been shown to attenuate alcohol self-administration [250, 251], morphine-induced dopamine release in the nucleus accumbens [252], and morphine-conditioned place preference [253]. Recent studies have begun to investigate these medications in humans.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…For opioids, based on preclinical evidence, central immune signaling is now a recognized contributor. Although not discussed here, other adverse actions of opioids, such as respiratory depression, addiction, and dependence are also associated with induction of central immune signaling (Hutchinson et al, 2007(Hutchinson et al, , 2008b(Hutchinson et al, , 2009a(Hutchinson et al, , 2010cBland et al, 2009;. Thus, to maintain the beneficial use of opioids, measures to minimize central immune signaling must be taken.…”
Section: What Are the Opportunities Provided By Pharmacological Tamentioning
confidence: 99%